1999
DOI: 10.1093/jn/129.10.1879
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-Like Growth Factor (IGF)-I Concentrations Are Reduced by Short-Term Dietary Restriction and Restored by Refeeding in Domestic Cats (Felis catus)

Abstract: Nutritional modulation of insulin-like growth factors (IGF) and their binding proteins (IGFBP) is well established. The effect of nutritional restriction on the serum IGF/IGFBP system of adult cats was investigated to evaluate serum IGF-I as a biochemical marker of nutritional status. Assays for measuring feline serum IGF and IGFBP were validated and normal ranges established in a study population of 46 healthy nonobese adult cats. Serum concentrations of IGF-I and IGF-II correlated significantly with body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…A 29 kDa band has been previously identified as IGFBP-1 in cats by immunoblotting [25]. In our study, the density of 29 kDa protein band was found as decreased in insulin-treated cats whereas the density of 25 kDa protein band increased in diabetic compared to insulin-treated cats.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A 29 kDa band has been previously identified as IGFBP-1 in cats by immunoblotting [25]. In our study, the density of 29 kDa protein band was found as decreased in insulin-treated cats whereas the density of 25 kDa protein band increased in diabetic compared to insulin-treated cats.…”
Section: Discussionsupporting
confidence: 66%
“…Four of these are important in human serum (IGFBP-1 to 4) in which IGF-I is predominantly bound to IGFBP-3 [32]. On the other hand, a previous study [25] reported that IGFBP-3 appears as doublet (39 and 43 kDa) in cats. Lewitt et al [22] has also reported that cat serum contains IGFBP-3 doublets bands with molecular masses of approximately 45 kDa and 25~35 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…None of the enrolled cats had evidence of impaired liver or kidney function on these blood tests. We closely monitored food intake during the study because short‐term fasting can decrease serum IGF‐1 concentration in cats . Fortunately, none of the cats in the study experienced noticeable decrease in caloric intake during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Serum IGF-I concentration is generally considered as a biochemical marker of nutritional status and correlates significantly with BW in cats and dogs (Eigenmann et al, 1984;Maxwell et al, 1999). Because normally IGF-I levels reflect the growth hormone (GH) status and because GH secretion is decreased in obesity, it has been suggested that IGF-I is stimulated by the hyperinsulinism that is very often present in the obese state (Clemmons and van Wyk, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Because normally IGF-I levels reflect the growth hormone (GH) status and because GH secretion is decreased in obesity, it has been suggested that IGF-I is stimulated by the hyperinsulinism that is very often present in the obese state (Clemmons and van Wyk, 1984). Furthermore, IGF-I is reduced by fasting or by short-term dietary restriction in cats (Maxwell et al, 1999). In the present trial, we did not observe significant variations of IGF-I, nor insulin concentrations during the weight loss programme.…”
Section: Discussionmentioning
confidence: 99%